Wayward Sisters. A Germanic Narrative Structure as Building Blocks in Two Íslendingasǫgur - Ventura, Ambra (Folia Scandinavica Posnaniensia, 2025)
This article focuses on the role and evolution of the Female Avenger in the Íslendingasǫgur, its patterns and narrative structure, by analysing and comparing two episodes from Gísla saga Súrssonar and Harðar saga. Þórdís (Gísla) and Þorbjǫrg (Harðara) draw upon an earlier Germanic archetype, best exemplified by Guðrún Gjúkadóttir, bringing about vengeance at the dinner table. However, where they differ is in the aftermath of said dinner. Building on the foundations laid by Guðrún, these two women set themselves apart from most other female characters by taking revenge into their own hands, instead of recurring to the usual, codified ways of getting revenge through inciting male relatives into doing it. Their brothers are their keystones, and their complex relationships make or break Germanic narrative structures. The turning point comes when both women betray their brothers, leading to their husbands having their brothers-in-law killed, news of the killing reaching the women at the dinner table, and the consequent decision to violently avenge their brothers. The reason for the appearance of this new structure might be found in a cultural shift, it might be purely narratological, or a mix of both. This paper seeks to answer this question.